PENGARUH PENGGUNAAN MEDIA GOOGLE EARTH UNTUK MENINGKATKAN BERPIKIR SPASIAL SISWA PADA MATA PELAJARAN GEOGRAFI DI SMAN 2 PADANG PANJANG - Yurni Suasti; Nelly (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the application of the use of google earth media to improve students' spatial thinking skills and to determine the effect of using google earth media to improve students' spatial thinking skills at SMAN 2 Padang Panjang. The research method used in this study is the Quasi Experiment Method with the research design of Nonequivalent Control Group Design. Sampling was done by Random Sampling technique. The samples in this study were X.1 class students as the experimental class given the Google Earth application learning media treatment and X.2 class as the control class given the Microsoft Power Point learning media treatment. Data collection uses multiple-choice pretest and posttest instruments that have been tested for validity, reliability, and observation. The results of this study are that there is an effect of Google Earth Learning Media on the spatial thinking ability of students in class X.1 SMA N 2 Padang Panjang, the average posttest of the experimental class is 84.59 and the control class is 70.73. Data analysis using the paired Sample T-Test test from the calculated data obtained a significance level (Sig.) of 0.001 because the significance is smaller than 0.005 (0.001 <0.005), then Ho is rejected and Ha is accepted.